Presence of Resistant DEC Strains in a Tertiary Healthcare Center in North East India in Children under 18 Years - Prasad, Abhijit Kumar; Lyngdoh, Wihiwot Valarie; Devi, Thigujam Surbala; Durairaj, Elantamilan (Journal of Laboratory Physicians, 2022)
Introduction Diarrheal illness such as diarrheagenic Escherichia coli (DEC), apart from rotavirus, is a common etiological agent known to cause moderate-to-severe diarrhea in low-income countries where unregulated use of antibiotics is rampant, giving rise to multidrug resistant (MDR) strains. This study is an earnest effort in reflecting the resistance pattern in such isolates.Materials and Methods It is a hospital-based cross-sectional study conducted over a period of 1 year (January to December, 2015). Children aged less than 18 years presenting with (n = 170) and without (n = 47) diarrhea were included as cases and controls, respectively. Fresh stool sample from eligible participants was collected and inoculated on MacConkey agar. Based on the colony morphology and biochemical identification followed by polymerase chain reaction (PCR), different pathotypes of DEC were identified. All such isolates were subjected to antimicrobial susceptibility testing employing VITEK 2 identification system. The result of the tested antibiotics was evaluated as per Clinical and Laboratory Standards Institute 2015 guidelines.Results DEC with specific virulence genes were detected by multiplex real-time PCR in 39 and 3 children with or without diarrhea, respectively. Most common DEC pathotypes found were enteroaggregative E. coli (38%) followed by enteropathogenic E. coli (28.5%). MDR isolates comprised 35 of 42 DEC pathotypes (83.3%). Resistance among DEC pathotypes to ampicillin, amoxicillin–clavulanate, ciprofloxacin, cephalosporin, nalidixic acid, imipenem, and cotrimoxazole was found to be statistically significant in comparison to non-DEC isolates.Conclusion This study has highlighted the increased prevalence of MDR strains among DEC pathotypes. Looking for these isolates will help detect dreadful DEC pathotypes like enterohemorrhagic E. coli where early administration of a sensitive antibiotic will go a long way in preventing complication like hemorrhagic colitis and hemolytic uremic syndrome.
Keywords: children under 18 years; DEC; diarrheagenic Escherichia coli; MDR strains; MDR-DEC; North East India; resistant DEC